Neurotensin Decreases the Proinflammatory Status of Human Skin Fibroblasts and Increases Epidermal Growth Factor Expression - Lucília Pereira da Silva; Bruno Miguel Neves; Liane Moura; Maria Teresa Cruz; Eugénia Carvalho (Hindawi Limited, 2014)
Fibroblasts colonization into injured areas during wound healing (WH) is responsible for skin remodelling and is also involved in the modulation of inflammation, as fibroblasts are immunologically active. Herein, we aimed to determine neurotensin effect on the immunomodulatory profile of fibroblasts, both in homeostatic and inflammatory conditions. Neurotensin mediated responses occurred through NTR1 or NTR3 receptors, while under inflammatory conditions NTR1 expression increase seemed to modulate neurotensin responses. Among different immunomodulatory genes, CCL11, IL-8, and IL-6 were the most expressed genes, while CCL4 and EGF were the less expressed genes. After neurotensin exposure, IL-8 mRNA expression was increased while CCL11 was decreased, suggesting a proinflammatory upregulation and chemoattractant ability downregulation of fibroblasts. Under inflammatory conditions, gene expression was significantly increased. After neurotensin exposure, CCL4 and IL-6 mRNA expression were decreased while CCL11 was increased, suggesting again a decrease in the chemoattractant capacity of fibroblasts and in their proinflammatory status. Furthermore, the expression of EGF, a crucial growth factor for skin cells proliferation and WH, was increased in all conditions. Overall, neurotensin, released by nerve fibers or skin cells, may be involved in the decrease of the chemotaxis and the proinflammatory status in the proliferation and remodelling phases of WH.